SOCIETY EMPOWERMENT AS A STRUNGGLE TO DEVELOP DIWAK TOURISM VILLAGE IN SEMARANG REGENCY - Tiara Lusy K; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Diwak Village is a potential tourist village that has empowerment activities in developing tourism potential. Empowerment of tourist villages Diwak uses the concept of the pentahelix approach involving 5 elements, namely academics, business, community, government and media, but the involvement of the implementation of empowerment is not in line with expectations. This study aims to analyze the synergy of stakeholders through the role of each stakeholder involved in empowerment activities. The research method used is a qualitative method with data collection techniques of observation, interviews, and documentation. Determination of research subjects use purposive sampling techniques and being followed by snowball sampling techniques and data validity with data triangulation techniques. The results show that the stakeholders involved are: Semarang State University, PT. Sidomuncul, Empowerment Service, Tourism Office, Diwak Village Karangtaruna, and Diwak Village Website. The empowerment process is carried out by motivating, mentoring, training and providing supporting facilities to the community. However, the role of each stakeholder in implementing the empowerment of the tourist village of Diwak has not been optimally implemented. The realization of the synergy between stakeholders in the community empowerment of tourism villages in Diwak has not been realized because the relationship of cooperation and coordination among stakeholders does not work well. The passive stakeholdersin coordinatingprocess are the Kelurahan Diwak Website, Empowerment Service and Tourism Office. Suggestions can be given is to improve the relationship of cooperation, coordination, and communication among the 5 stakeholders in implementing the empowerment of Diwak tourism village through a more intensive village tourism activist forum within two years to establish coordination creating synergy for the success of empowerment